Volatolomics approach for authentication of not-from-concentrate (NFC) orange juice based on characteristic volatile markers using headspace solid phase microextraction (HS-SPME) combined with GC-MS. (June 2022) - Zhang, Jiukai; Liu, Hanlu; Sun, Ruixue; Zhao, Yan; Xing, Ranran; Yu, Ning; Deng, Tingting; Ni, Xue; Chen, Ying
Abstract: The not-from-concentrate (NFC) juice is gradually becoming popular with consumers. However, adulteration of NFC juice with low-priced from-concentrate (FC) juice has been a long-lasting concern. In the present study, a volatolomics approach for authentication of NFC orange juice based on volatile organic compounds (VOCs) was established. A total of 107 VOCs were identified by solid phase microextraction (SPME) GC-Q-Exactive Orbitrap. Discrimination of NFC and FC orange juice could be accomplished by orthogonal partial least squares discriminant analysis (OPLS-DA). Furthermore, 10 VOCs were selected as potential characteristic markers in different juices, including 4 esters, 5 alcohols and 1 ketone. In addition, 13 VOCs with significant quantitative difference was also screened. A partial least squares discriminant analysis (PLS-DA) model based on the above 23 VOCs achieved accuracy of 100% and 95.6% for calibration and prediction set, respectively. These results suggested that the volatolomics approach has great potential for authentication of NFC juice. Highlights: Volatolomics reveals the differences of VOCs between NFC and FC orange juice. Discrimination of NFC and FC orange juice could be accomplished by OPLS-DA. 10 VOCs were selected as characteristic markers in different juice. 13 VOCs with significant quantitative difference was screened. PLS-DA based on above 23 VOCs has high classification accuracy in different juice.